De jure and de facto democracy in post-socialist countries - Lewkowicz, Jacek; Metelska-Szaniawska, Katarzyna (Publishing House of Wroclaw University of Economics and Business, 2022)
Are de jure rules that formally shape democratic systems relevant for the actual condition of democracy? The authors pose this question with regard to post-socialist countries of Europe and Asia and their experiences with democracy since the beginning of their transition process, and the contribution consists in extending the focus to de jure institutions underpinning de facto democratization and economic performance of these countries. The empirical part employs panel data regression techniques to identify whether certain de jure rules of democracy established in the new post-socialist constitutions after 1989 were significant for these countries’ ‘democratic performance’ during transition. The authors relate, in particular, to core components of electoral democracy, as well as to some aspects of its participatory dimension.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 131-161
Keywords: democracy; de jure and de facto institutions; post-socialist transition